Critical Notes on the ‘Chronica’ of Sulpicius Severus - Hyltén, Per (Traditio, 1963)
In the course of preparing for the Corpus Christianorum an edition of the Chronica of Sulpicius Severus I have come upon nearly a dozen passages in which the adopted reading invited discussion beyond the limits of an apparatus criticus. This discussion is supplied in the following notes, which may be seen as a supplement to similar treatment of many other passages in the Chronica that are found in my doctoral dissertation, Studien zu Sulpicius Severus (Lund 1940). As an appendix appears a discussion of a few passages in the writings of Sulpicius Severus on St. Martin of Tours; this too looks to the new edition of the text that is to appear in the Corpus Christianorum (where I have the collaboration of Dr. Bernard M. Peebles) but is especially prompted by a recent criticism of my dissertation.